Constraints on the cerebral basis for semantic processing from neuroimaging studies of Alzheimer's disease. Issue 2 (1st August 1997) - Grossman, Murray; Payer, Franz; Onishi, Kris; White-Devine, Tammy; Morrison, Donald; D'Esposito, Mark; Robinson, Keith; Alavi, Abass
Abstract : OBJECTIVE: Functional activation studies of semantic processing in healthy adults have yielded conflicting results. The purpose was to evaluate the relative role of the brain regions implicated in semantic processing with converging evidence from imaging studies of patients with impaired semantic processing. METHODS: Semantic memory was assessed in patients with Alzheimer's disease using two measures, and these performance patterns were related to profiles of reduced cerebral functioning obtained with high resolution single photon emission computed tomography (SPECT). Patients with frontotemporal degeneration were similarly evaluated as a control group. RESULTS: Reduced relative cerebral perfusion was seen in parietal and posterior temporal brain regions of patients with Alzheimer's disease but not patients with frontotemporal degeneration. Impairments on semantically guided category membership decision tasks were also seen in patients with Alzheimer's disease but not those with frontotemporal degeneration. Performance on the semantic measures correlated with relative cerebral perfusion in inferior parietal and superior temporal regions of the left hemisphere only in Alzheimer's disease. Relative perfusion was significantly lower in these regions in patients with Alzheimer's disease with semantic difficulty compared with patients with Alzheimer's disease with relatively preserved semantic processing. CONCLUSION: These findings provide converging evidence to support the contribution of superior temporal and inferior parietal regions of the left hemisphere to semantic processing.